Impact of temperature on yield and related traits in cotton genotypes - Kalim Ullah; Niamatullah Khan; Zahid Usman; Rehmat Ullah; Fazal Yazdan Saleem; Syed Asif Imran Shah; Muhammad Salman (Journal of Integrative Agriculture, 2016)
Cotton growth and development is influenced by various uncontrollable environmental conditions. Temperature variations in the field can be created by planting at different dates. The objective of the present study was to evaluate the effect of planting dates and thermal temperatures (growing degree days) on yield of 4 cotton genotypes, viz., CIM-598, CIM-599, CIM-602 and Ali Akbar-703. Plants were subjected to 6 planting dates during 2013 and 2014 in a trial conducted in randomized complete block design with four replications. For boll number, boll weight and seed cotton yield, cotton genotypes exhibited significant differences, CIM-599 produced the highest seed cotton yield of 2062 kg ha–1 on account of maximum boll number and boll weight. The highest seed cotton yield was recorded in planting dates from 15th April to 1st May whereas early and delayed planting reduced the yield due to less accumulation of heat units. Regression analysis revealed that increase of one unit (15 days) from early to optimum date (15th March to 15th April) increased yield by 93.58 kg ha–1. Delay in planting also decreased the seed cotton yield with the same ratio. Thus it is concluded that cotton must be sown from 15th April to 1st May to have good productivity in this kind of environment.